The Role of Parental Assistance in the Learning Motivation and Discipline of Elementary School Students during the Covid-19 Pademic Period - Ni Komang Nanda Mega Utami; I Made Citra Wibawa; I Gede Astawan (Universitas Pendidikan Ganesha, 2022)
The problems that currently arise in online learning are of various variations, such as the lack of motivation, interest, and low discipline of children. Parents can be teachers to children in their spare time, but parents feel anxious to do so because of a lack of experience. This study aims to analyzed parental assistance's role in student motivation and learning discipline in elementary schools during the COVID-19 pandemic. This type of research is descriptive qualitative with a phenomenological approach. The primary data sources in this study were parents, second grade students, and homeroom teachers for grade II who were informants/subjects of the research. The sampling technique in this study used purposive sampling. Collecting data from this study was obtained by observation and interviews. The instrument used to collect data is an interview sheet. In this qualitative research, the researcher used the data analysis technique carried out in four stages, namely: data collection, data reduction, data presentation, and verification/drawing conclusions. Triangulation is also used as a multi-method approach when collecting and analyzing data. The study's results, namely the role of parental assistance in learning motivation and discipline in students during the Covid-19 pandemic, were shown by various efforts. First, parents provide learning facilities for children to participate in online learning. Second, parents always accompany and support learning activities at home. Third, parents set an excellent example for their children. It was concluded that the role of reasonable parental assistance could increase motivation and learning discipline in students during the Covid-19 pandemic.